Quintets, Quartets, Movements and Fragments [de Wolfgang Amadeus Mozart] : Stringas and Wind = Quintets, Quartets, Movements and Fragments [de Wolfgang Amadeus Mozart] : Kammermusik für Streicher un Bläser = Quintets, Quartets, Movements and Fragments [de Wolfgang Amadeus Mozart] : musique de chambre pour cordes et vents = Quintets, Quartets, Movements and Fragments [de Wolfgang Amadeus Mozart] : musica da camera per archi e fiati - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: 1) Clarinet Quintet in A, KV 581; 2) Horn Quintet in E Flat, KV 407/386c; 3) Oboe Quartet in F, KV 370/368b; 4) Sonata for Bassoon and Cello in B FLat, KV 292/196c; 5) Flute Quartet in D, KV 285; 6) Flute Quartet in A, KV 298; 7) Flute Quartet in C, KV App. 171/285b; 8) Flute Quartet in G, KV 285a; 9) 10 Movements and Fragments for Chamber Ensemble, KV 174, KV 168a, KV 288/246c, KV App. 68/589a for a String Quartet, KV App. 72/464a for a String Quartet, Kv App. 80/514a for a String Quartet, KV App. 90/580b; KV App. 66/562e for a String Trio, KV App. 91/516c for a Clarinet Quintet, KV App. 79 for a String Quintet.